Customer Engagement as a Mediating Mechanism between Social Media Marketing and Brand Loyalty in Culinary SMEs - Elda Andrialya Putri; Amran Wahyudiah; Dewi Rosita; Nurlia Nurlia (Journal of Marketing Management and Innovative Business Review, 2026)
This study examines the role of Customer Engagement as a mediating mechanism in the relationship between Social Media Marketing and Brand Loyalty in culinary SMEs. Using a quantitative approach, data were collected from 150 SME owners and managers in Balikpapan, East Kalimantan, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that Social Media Marketing has a positive and significant effect on Customer Engagement, although the effect is moderate. Customer Engagement is found to have a strong and significant influence on Brand Loyalty, indicating its critical role in building long-term customer relationships. Meanwhile, the direct effect of Social Media Marketing on Brand Loyalty is positive but relatively weak. Mediation analysis confirms that Customer Engagement significantly mediates the relationship between Social Media Marketing and Brand Loyalty. These findings suggest that social media activities alone are insufficient to generate strong customer loyalty unless they are able to foster meaningful engagement. The study contributes to the literature by emphasizing the importance of engagement as a key mechanism in digital marketing, particularly in the SME context. Practically, the results highlight the need for SMEs to focus on interactive and relationship-oriented strategies to enhance customer loyalty